Low-energy shockwave therapy in the management of wound healing following Fournier’s gangrene: case report - Rassweiler, Jens; Scheitlin, Walter; Gözen, Ali Serdar; Rassweiler-Seyfried, Marie-Claire (European urology open science, 2022)
We report on postoperative management of wound healing in four cases of Fournier’s gangrene successfully treated with low-intensity shockwave therapy (LI-ESWT). In three cases, LI-ESWT (3 sessions per week with 2000 shockwaves at 3 Hz applied at 0.25 mJ/mm2) was able to close wound dehiscence secondary to plastic surgery with skin flaps. In one patient, LI-ESWT resulted in complete closure of an extensive wound with restoration of the local scrotal and penile skin. This is the first report of successful application of LI-ESWT for this indication. Restoration of local skin rather than wound closure by fibrous tissue could be related to promotion of stem cells, which has been discussed previously for other indications, such as treatment of chronic ulcers and restoration of the pelvic floor.